2018
DOI: 10.1038/s41467-018-03131-0
|View full text |Cite
|
Sign up to set email alerts
|

Aggregating sequences that occur in many proteins constitute weak spots of bacterial proteostasis

Abstract: Aggregation is a sequence-specific process, nucleated by short aggregation-prone regions (APRs) that can be exploited to induce aggregation of proteins containing the same APR. Here, we find that most APRs are unique within a proteome, but that a small minority of APRs occur in many proteins. When aggregation is nucleated in bacteria by such frequently occurring APRs, it leads to massive and lethal inclusion body formation containing a large number of proteins. Buildup of bacterial resistance against these pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
124
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(128 citation statements)
references
References 47 publications
(48 reference statements)
4
124
0
Order By: Relevance
“…They were also found to be lethal to bacterial cells [14,15]. Their specific toxicity toward bacterial and not mammalian cells involves uptake mechanisms and specific cross-aggregation with bacterial homologous sequences; this cross-aggregation subsequently leads to disruption of bacterial protein homeostasis as a result of the accumulation of protein aggregates [14,15]. Elucidating the mechanism of antimicrobial action of the two peptides reported here will be the subject of future studies.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…They were also found to be lethal to bacterial cells [14,15]. Their specific toxicity toward bacterial and not mammalian cells involves uptake mechanisms and specific cross-aggregation with bacterial homologous sequences; this cross-aggregation subsequently leads to disruption of bacterial protein homeostasis as a result of the accumulation of protein aggregates [14,15]. Elucidating the mechanism of antimicrobial action of the two peptides reported here will be the subject of future studies.…”
Section: Discussionmentioning
confidence: 80%
“…Cationic aggregating peptides comprising arginine residues, as well as short aggregation-prone residue stretches, were recently identified via bioinformatics approaches in the bacterial proteome and were reported to internalize in mammalian cells. They were also found to be lethal to bacterial cells [14,15]. Their specific toxicity toward bacterial and not mammalian cells involves uptake mechanisms and specific cross-aggregation with bacterial homologous sequences; this cross-aggregation subsequently leads to disruption of bacterial protein homeostasis as a result of the accumulation of protein aggregates [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, it has also been shown that the introduction of point mutations that abolish the aggregation propensity of an APR is sufficient to reduce the aggregation propensity of the entire protein (Ganesan et al, 2016;Marshall et al, 2016). Finally, short peptides solely coding for such APRs are able to induce the aggregation of a full-length protein comprising that APR Khodaparast et al, 2018;Betti et al, 2016). APRs generally only present a danger for aggregation in situations where proteins are partially or totally unfolded, such as during protein translation or translocation, under situations of physiological stress, or due to mutations that destabilize the native conformation.…”
Section: Introductionmentioning
confidence: 99%